2008
DOI: 10.1021/je800152d
|View full text |Cite
|
Sign up to set email alerts
|

Ion Pair Formation of Alkylimidazolium Ionic Liquids in Dichloromethane

Abstract: The 1:1 ion pair formation constants (K IP 0 ) of 1-alkyl-3-methylimidazolium ([RMeIm] + ; R ) butyl, hexyl, and octyl) and 1-butyl-2,3-dimethylimidazolium ([BuMe 2 Im] + ) ions with tetrafluoroborate ([BF 4 ] -), hexafluorophosphate ([PF 6 ] -), bis(trifluoromethanesulfonyl)amide ([NTf 2 ] -), and 2,4,6-trinitrophenolate (picrate, [Pic] -) ions have been determined conductometrically in dichloromethane at 25 °C. The K IP 0 determinations have also been made for symmetric tetraalkylammonium ions ([R 4 N] + ; R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 21 publications
9
70
1
Order By: Relevance
“…As seen in Table 1, we can confirm that the molar volume in the ILs becomes larger as the cation and anion become heavier. Although the self-diffusion, interionic interaction, and ion-pair formation do not always correlate to the ionic volume (Tsuzuki et al, 2005;Katsuta et al, 2008), it is suggested that discussing the interionic interaction with the effect of the ion volume is appropriate when comparing the present ions because the structures of the ions are relatively less influenced by a heavy atom substitution compared to the case in which a whole ion is exchanged. Polarizability is another factor responsible for the intermolecular (or interionic) interaction.…”
Section: Target Ionic Liquids Electronic Structures and Static Propmentioning
confidence: 99%
“…As seen in Table 1, we can confirm that the molar volume in the ILs becomes larger as the cation and anion become heavier. Although the self-diffusion, interionic interaction, and ion-pair formation do not always correlate to the ionic volume (Tsuzuki et al, 2005;Katsuta et al, 2008), it is suggested that discussing the interionic interaction with the effect of the ion volume is appropriate when comparing the present ions because the structures of the ions are relatively less influenced by a heavy atom substitution compared to the case in which a whole ion is exchanged. Polarizability is another factor responsible for the intermolecular (or interionic) interaction.…”
Section: Target Ionic Liquids Electronic Structures and Static Propmentioning
confidence: 99%
“…It results from the fact that the relative permittivity of dichloromethane is low, its ionization properties are relatively weak, and electrolytes dissolved in DCM are strongly associated [11][12][13][14][15]. Therefore, it is necessary to use the extremely low concentrations of the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…8 Water was deionized with a Milli-Q Labo system (Millipore) after distillation. Dichloromethane (Kanto Chemical, GR grade) was washed with deionized water for three times.…”
Section: Reagentsmentioning
confidence: 99%
“…The cation dependence of the ion-pair formation constant in dichloromethane reflects that of the direct cation-anion interaction in the gas phase. 8,9 It can therefore be concluded that the direct cation-anion interaction is also a major factor determining the larger aqueous ion-pair formation constants for RMeIm + compared to those for R4N + .…”
Section: Transfer Activity Coefficients Of Ionsmentioning
confidence: 99%
See 1 more Smart Citation